PERAN RELAWAN DEMOKRASI (RELASI) SEBAGAI “ELECTION MARKETER”: (Studi Kasus Pemilihan Umum Legislatif 2014 di Kabupaten Pasuruan) - M. Daimul Abror; Heri Sunarno (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2017)
The voter turnout 3 last period (1999-2009) has decreased significantly. At 1999 92.6% choseen and 7.3% abstains, at 2004 84.1% choseen and 15.9% abstains, at 2009 70.9% choosen and 29.1% abstains. (www.merdeka.com). These conditions encourage KPURI to form Volunteer Democracy (VD) as an agent that helps the socialization of Election 2014. This study aims to comprehensively assess the role of VD as "Election Marketer" in Principal Agency Theory (PAT) perspective. This study uses qualitative research with case study approach. The results are (1) Relation between KPUD Pasuruan with VD is KPUD Pasuruan (principal) provide delegates to VD (agent) (2). Contract model of VD in two aspects, the type of contract that the contract model is short Term Contracts, and the type of both relationship are relation between government and civil society; (3) In carrying out its role as election marketer, VD fulfill four criteria in PAT perspective. The weakness of the model contract of VD are Short Term Contracts must be solved by entering into a Long Term Contracts to be interwoven communication simultaneously between the government in this case between KPUD Pasuruan with VD as the embodiment of Civil Societies participation is represented by five segments groups of voters.